PENGARUH SELF ASSESSMENT SYSTEM DAN PEMERIKSAAN PAJAK TERHADAP PENERIMAAN PAJAK PERTAMBAHAN NILAI (Studi pada KPP Pratama Boyolali tahun 2013 – 2018) - Jayanti, Zeny; Harimurti, Fadjar; Kristianto, Djoko (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2019)
The purpose of this study was to analyze the significance of the effect of self assessment system and tax audit, in addition to knowing among the self assessment system and tax audit variables that were the dominant influence on value added tax receipts at KPP Pratama Boyolali. The type of data used is quantitative data. The data source used is secondary data. The entire population in this study were all PKP registered at KPP Pratama Boyolali with the sampling technique using purposive sampling method. The data collection technique in this study uses documentation. Data analysis techniques used, Classical Assumption Test, Multiple Linear Regression Analysis, t Test, F Test (Model Accuracy), and Determination Coefficient Test (R2). The results of this study indicate that the Self Assessment System and Tax Examination affect the value added tax revenue at KPP Pratama Boyolali. The results of the coefficient of determination (R2) is 0,221, this means that the contribution or influence given by the self assessment system variable and tax audit on the receipt of VAT is 22,1% while the remaining 77,9% is influenced by other variables outside the variables studied, Tax Collection, Issuance of Forced Letters, Exchange Rates, Inflation and so on.